Comparative Study of Free and Encapsulated Hypocrellin B on Photophysical-Chemical Properties, Cellular Uptake, Subcellular Distribution, and Phototoxicity - Weiyan Kang; Feng Zhao; Jixing Cheng; Kaijie Feng; Liang Yan; Yue You; Jinxia Li; Jing Meng (Nanomaterials)
The present study compared the free and encapsulated photosensitizer hypocrellin B (HB) in terms of photophysical-chemical properties, cellular uptake, subcellular distribution, and phototoxicity. The hydrophobic HB was encapsulated into liposomes (HB@Lipo) or poly (lactic-co-glycolic acid) nanoparticles (HB@PLGA). Encapsulation into nanocarriers exerted no obvious influence on the photophysical-chemical properties of HB, including UV-visible absorbance, fluorescence spectra, singlet oxygen (1O2) production capacity, and photostability. Free and encapsulated HB revealed some disparities in cellular uptake and subcellular localization patterns. In 2D-cultured B16 cells and tumor spheroids, free HB exhibited the fastest cellular uptake, while HB@PLGA had the lowest, as evidenced. Subcellular localization analysis first revealed a significant colocalization of free HB, HB@Lipo, and HB@PLGA within lipid droplets, with minimal colocalization in mitochondria and the endoplasmic reticulum. Unlike free HB and HB@Lipo, HB@PLGA exhibited strong lysosomal colocalization, indicating a unique intracellular trafficking pathway for PLGA-encapsulated HB. Upon laser irradiation, both free and encapsulated HB induced pronounced phototoxicity with substantial ROS production, confirming the robust PDT effect of HB. The photodynamic killing effect correlated with the intracellular HB content. These findings highlighted the impact of nanoformulation on HB’s cellular behavior and therapeutic performance.